Rancang Bangun Generator Termoelektrik Dengan Metode Efek Seebeck Sebagai Alternatif Pembangkit Energi Listrtik - Sari, Nurma; Sugriwan, Iwan; Sari, Nor Dewi (Universitas Lambung Mangkurat, 2024)
One of the alternative technologies for generating electrical energy is a thermoelectric generator using the Seebeck effect method. This study aims to determine the effect of measuring angles and distances on the value of the Seebeck coefficient. This design consists of six peltier type TEC1-12706 in series and parallel, two digital multimeters to read voltage and current given a 10 ohm resistor, two DS18B20 sensors. waterproof to read the temperature from both sides of the thermoelectric with an aluminum plate on the hot side and a heatsink equipped with a 12 volt dc fan on the cold side, 20 x 4 character LCD, SD card module, RTC module and Arduino UNO R3 microcontroller. Tool temperature is made to get the comparison results obtained with an average error value with a range of 200C -100 0C of 1.330C sensor 1 and 1.150C sensor 2 and seen from the standard error value of the statistical test comparison of measuring instruments is 0.04 and 0.06. The design that has been made uses the Arduino IDE program to program and display data on the LCD and the RTC and SD card modules are used to display data in real time and store temperature data in the form of a notepad. Based on measurements of the thermoelectric output value with an angle of 600,900,1200,1500 and 1800 and distances of 5, 10, 15 and 20 cm using the heat source of the ironing elements positioned from the top, bottom and sides. The thermoelectric can produce a voltage of 0.22910 V and a current of 0.01238 A. The heater position from the side is connected in series and 0.05450 V, the current is 0.00261 A from the bottom in parallel which is obtained from the best angle of 600 at adistance of 5 cm.